Comparison of Library of Plans with two daily adaptive strategies for whole bladder radiotherapy. (October 2021) - den Boer, Duncan; den Hartogh, Mariska D.; Kotte, Alexis N.T.J.; van der Voort van Zyp, Jochem R.N.; Noteboom, Juus L.; Bol, Gijsbert H.; Willigenburg, Thomas; Werensteijn-Honingh, Anita M.; Jürgenliemk-Schulz, Ina M.; van Lier, Astrid L.H.M.W.; Kroon, Petra S.
Abstract: Background and purpose: Whole bladder radiotherapy is challenging due to inter- and intrafraction size and shape changes. To account for these changes, currently a Library of Plans (LoP) technique is often applied, but daily adaptive radiotherapy is also increasingly becoming available. The aim of this study was to compare LoP with two magnetic resonance imaging guided radiotherapy (MRgRT) strategies by comparing target coverage and volume of healthy tissue inside the planning target volume (PTV) for whole bladder treatments. Methods and materials: Data from 25 MRgRT lymph node oligometastases treatments (125 fractions) were used, with three MRI scans acquired at each fraction at 0, 15 and 30 min. Bladders were delineated and used to evaluate three strategies: 1) LoP with two plans for a 15 min fraction, 2) MRgRT15min for a 15 min fraction and 3) MRgRT30min for a 30 min fraction. The volumes of healthy tissue inside and bladder outside the PTV were analyzed on the simulated post-treatment images. Results: MRgRT30min had 120% and 121% more healthy tissue inside the PTV than LoP and MRgRT15min . For LoP slightly more target outside the PTV was found than for MRgRT30min and MRgRT15min, with median 0% (range 0–23%) compared to 0% (0–20%) and 0% (0–10%), respectively. Conclusions: Taking into account both target coverage and volume of healthy tissue inside the PTV, MRgRT15min performed better than LoP and MRgRT30min for whole bladder treatments. A 15 min daily adaptive radiotherapy workflow is needed to potentially benefit from replanning compared to LoP.